Micro-scaffolds as synthetic cell niches: recent advances and challenges. (February 2022) - Weißenbruch, Kai; Lemma, Enrico D; Hippler, Marc; Bastmeyer, Martin
Graphical abstract: Highlights: 3D scaffolds with unprecedented physico-chemical properties can be microfabricated. Hydrogels, synthetic polymers, and fibrous materials can be patterned in 2D and 3D. ECM-like conditions are mimicked, allowing for (stem) cell culture. Insights on the interaction of various stem cell types with scaffolds are reviewed. Examples of 3D and 4D scaffolds for basic cell biological research are reported. Abstract : Micro-fabrication and nano-fabrication provide useful approaches to address fundamental biological questions by mimicking the physiological microenvironment in which cells carry out their functions. In particular, 2D patterns and 3D scaffolds obtained via lithography, direct laser writing, and other techniques allow for shaping hydrogels, synthetic polymers and biologically derived materials to create structures for (single) cell culture. Applications of micro-scaffolds mimicking cell niches include stem cell self-renewal, differentiation, and lineage specification. This review moves from technological aspects of scaffold microfabrication for cell biological applications to a broad overview of advances in (stem) cell research: achievements for embryonic, induced pluripotent, mesenchymal, and neural stem cells are treated in detail, while a particular section is dedicated to micro-scaffolds used to study single cells in basic cell biology.